Synthesis, anti-inflammatory, cytotoxic, and COX-1/2 inhibitory activities of cyclic imides bearing 3-benzenesulfonamide, oxime, and β-phenylalanine scaffolds: a molecular docking study - Alaa A.-M; Adel S. El-Azab; Nawaf A. AlSaif; Mohammed M. Alanazi; Manal A. El-Gendy; Ahmad J. Obaidullah; Hamad M. Alkahtani; Abdulrahman A. Almehizia; Ibrahim A. Al-Suwaidan (Taylor & Francis Group, 2020)
Cyclic imides containing 3-benzenesulfonamide, oxime, and β-phenylalanine derivatives were synthesised and evaluated to elucidate their in vivo anti-inflammatory and ulcerogenic activity and in vitro cytotoxic effects. Most active anti-inflammatory agents were subjected to in vitro COX-1/2 inhibition assay. 3-Benzenesulfonamides (2-4, and 9), oximes (11-13), and β-phenylalanine derivative (18) showed potential anti-inflammatory activities with 71.2-82.9% oedema inhibition relative to celecoxib and diclofenac (85.6 and 83.4%, respectively). Most active cyclic imides 4, 9, 12, 13, and 18 possessed ED50 of 35.4-45.3 mg kg−1 relative to that of celecoxib (34.1 mg kg−1). For the cytotoxic evaluation, the selected derivatives 2-6 and 8 exhibited weak positive cytotoxic effects (PCE = 2/59-5/59) at 10 μM compared to the standard drug, imatinib (PCE = 20/59). Cyclic imides bearing 3-benzenesulfonamide (2-5, and 9), acetophenone oxime (11-14, 18, and 19) exhibited high selectivity against COX-2 with SI > 55.6-333.3 relative to that for celecoxib [SI > 387.6]. β-Phenylalanine derivatives 21-24 and 28 were non-selective towards COX-1/2 isozymes as indicated by their SI of 0.46-0.68.